Quaternary refugia and secondary contact in the southern boundary of the Brazilian subregion: comparative phylogeography of freshwater fish - Bruno, María Cecilia (2015)
Freshwater fish are an ideal model to illustrate how climate-tectonic changes affect the distribution of genetic variation. Freshwater bodies are extensively affected by environmental changes, with streams even changing their courses in the most extreme cases. Fortunately, this situation is reflected in the genetic composition of populations and may currently be inferred from the study of mitochondrial DNA molecular markers. Here we analyze and compare the phylogeographic patterns of the species Corydoras paleatus and Jenynsia multidentata at the southern limit of the Brazilian subregion. These basins are isolated in the current hydrogeographic pattern due to geologic and paleoclimatic changes. Our results support a concurrent pattern for both species. Some lineages have persisted in the area under adverse climate conditions, possibly in environmental refuges, while other lineages may have colonized the area later by means of paleodrainage connections. In addition, the presence of independent, greatly diverging lineages, even within the same watercourses, suggests secondary contact between these lineages. This work represents a first approach to understand how geologic and paleoclimatic changes have affected the distribution of genetic variation in the Southern Pampean Area.